1998
DOI: 10.1159/000040863
|View full text |Cite
|
Sign up to set email alerts
|

α-Thalassemia in the United Arab Emirates

Abstract: A neonatal screening survey of α-thalassemia (α-thal) among the United Arab Emirates (UAE) nationals was conducted on 418 consecutive cord blood samples. Our findings demonstrate that 49% of the cases studied were found with an α-globin gene defect. The gene frequency of the –α3.7 was 0.2847 and that of the –α4.2 was 0.0072. Four nondeletional α-thal mutations were found; αPA-1, αPA-2, Hb CS and α-5nt del with gene frequencies of 0.0036, 0.0012, 0.0024, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 19 publications
5
58
1
Order By: Relevance
“…The IVS2-1 (G>A) mutation which is second in frequency in Jordan, has not been detected in Cyprus, Gaza, or Algeria but otherwise has a distribution pattern generally opposite to the distribution pattern of the IVS1-110 mutation in the region. In Jordan, this mutation has an intermediate frequency between the highest value reported for this mutation in Kuwait and Saudi Arabia and the lowest frequency reported in Syria and Greece [37,49]. 5.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The IVS2-1 (G>A) mutation which is second in frequency in Jordan, has not been detected in Cyprus, Gaza, or Algeria but otherwise has a distribution pattern generally opposite to the distribution pattern of the IVS1-110 mutation in the region. In Jordan, this mutation has an intermediate frequency between the highest value reported for this mutation in Kuwait and Saudi Arabia and the lowest frequency reported in Syria and Greece [37,49]. 5.…”
Section: Discussionmentioning
confidence: 82%
“…Although the common frequent alleles in Jordan are generally similar to those found in other countries in the region, many rare alleles reported in the region were not detected in this study. These included codon 29 (C>T) reported in Lebanon and Yugoslavia [24,25,35], the 290-bp deletion reported in Lebanon, Syria, and Turkey [24][25][26][31][32][33], the 25-bp deletion reported in Lebanon, West Saudi Arabia, Kuwait, and United Arab Emirates (UAE) [16][17][18]24,25,[36][37][38], the Saudi Arabian IVS1-128 (T>G) [39], codon 44 (-C) reported in Kurdish Jews, UAE, and Tunisia [34,37,38,40], and the frame shift at codons 8/9 (+G) reported in Saudi Arabia, Kuwait, and Jordanians living in Saudi Arabia [17,18,36].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Sutcu et al [13] in which distribution of alpha-thalassemia mutations was investigated at Isparta province, -a 3.7 allele frequency was 5.55 %. -a 3.7 gene deletion is the most frequently seen mutations in West Asia countries including Iran (40-93 %), United Arab Emirates (28.4 %), Saudi Arabia (64 %), Oman (58.3 %), Tunisia (22.5 %), Jordan (43 %), and Israel (51 %) [14][15][16][17][18][19][20]. Similarly, a 3.7 gene deletion is the most frequently seen mutation in Europe with the allele frequencies of 58.2 % in Holland, 46.94 % in Sicily and 52.41 % in Spain [21].…”
Section: Discussionmentioning
confidence: 99%
“…A DNA-based newborn screening survey [El-Kalla and Baysal, 1998] found that 49% of the neonates had a mutation in at least one alpha globin gene. Molecular characterization (Table 3) showed that the gene frequency of the Àa 3.7 was 0.2847, and that of Àa 4.2 was 0.0072.…”
Section: A-thalassemiamentioning
confidence: 99%
“…Molecular characterization (Table 3) showed that the gene frequency of the Àa 3.7 was 0.2847, and that of Àa 4.2 was 0.0072. In addition, four nondeletional a-thalassemia mutations were found, alpha PA-1, alpha PA À2, HbCS, and alpha À5ntdel, with frequencies of 0.0036, 0.0012, 0.0024, and 0.0072, respectively [El-Kalla and Baysal, 1998]. Clinically, most of the compound heterozygotes due to deletional and nondeletional a-thalassemias were categorized phenotypically as very mild HbH disease [El-Kalla and Baysal, 1998].…”
Section: A-thalassemiamentioning
confidence: 99%